2002
DOI: 10.1001/jama.287.19.2534
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Woman's Own Birth Weight With Subsequent Risk for Gestational Diabetes

Abstract: In this large population-based study, a woman's own birth weight was strongly and inversely related to her risk of GDM, suggesting that early life factors may be important in the etiology of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
108
4
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(129 citation statements)
references
References 53 publications
(55 reference statements)
13
108
4
4
Order By: Relevance
“…Considering socioeconomic levels, Innes et al 21 did not find an association between gestational diabetes mellitus development and private or public insurance, occupation during pregnancy, or education of the parents of the pregnant woman at the time of her birth. However, they found an inverse association between the educational level of the pregnant woman and gestational diabetes mellitus, after adjustment for other social, economic and demographic factors.…”
Section: Socioeconomic Level/educationmentioning
confidence: 96%
See 3 more Smart Citations
“…Considering socioeconomic levels, Innes et al 21 did not find an association between gestational diabetes mellitus development and private or public insurance, occupation during pregnancy, or education of the parents of the pregnant woman at the time of her birth. However, they found an inverse association between the educational level of the pregnant woman and gestational diabetes mellitus, after adjustment for other social, economic and demographic factors.…”
Section: Socioeconomic Level/educationmentioning
confidence: 96%
“…Short stature associated to gestational diabetes mellitus had been found for all the groups in the crude analysis, although the association between Afro-Caribbean was not statistically significant 32 . On the other hand, studying several risks for the development of gestational diabetes mellitus, Di Cianni et al 33 and Innes et al 21 , respectively, in Italian and American populations, had also found a significant inverse association between height and gestational diabetes mellitus, even after adjustments for confounders.…”
Section: Heightmentioning
confidence: 98%
See 2 more Smart Citations
“…20 Birthweight may predict growth over the first years of life 21 and may be a risk factor for future medical conditions. 22,23 Our observation has been that a disproportionate percentage (>10%) of the newborns at our institution were designated as large for gestational age (LGA), which is usually assigned to newborns with birthweights above the 90th percentile for their gestational age. Since the LGA designation is associated with a greater risk of short-term morbidity, primarily hypoglycemia, 24 hyperbilirubinemia, polycythemia, 25 and obstetrical complications, 26 these newborns are often closely monitored, especially with repeated blood glucose determinations.…”
Section: Introductionmentioning
confidence: 99%